Examining Organizational Response and Employee Coping Behaviors amid the COVID-19 Pandemic - Teng-Calleja, Mendiola; Caringal-Go, Jaimee Felice; O. Manaois, Jason; Y. Isidro, Ma. Queenie; S. Zantua, Rae Mark (The Journal of Behavioral Science, 2020)
Using the crisis in context theory (CCT) as an ecological framework to understanding human behaviors, the study examined organizational responses and individual employee coping behaviors to mitigate the impact of the COVID-19 pandemic. Drawing from the perspectives of psychology, organization development, and management, the research examined dependent and independent organization and self-initiated actions that employees deemed helpful in coping with the effects of the crisis. Qualitative data were gathered through online survey from 216 employees in the Philippines, a developing country whose major cities were on community quarantine to minimize the spread of the pandemic. The study identified organizational actions or responses to help employees adapt to the COVID-19 crisis. These are: 1) flexible work arrangements, 2) mental health and well-being programs, 3) physical health and safety measures, 4) financial support, 5) provision of material resources, and 6) communication of short and long term plans. Findings also surfaced coping strategies at the individual employee level and how these relate to organizational initiatives. Seven themes emerged from the data- 1) task-focused coping, 2) stress management, 3) social coping, 4) cognitive strategies, 5) learning and development activities, 6) faith-oriented coping, and 7) maladaptive strategies. The analysis highlighted the interrelatedness of organizational responses and employee actions (e.g. how individual task/social coping behaviors were enabled by the company’s flexible work arrangements and provision of technological resources amidst physical distancing). Insights from the findings may orient organizational efforts to mitigate the impact of the pandemic as well as encourage and support positive employee coping behaviors.